The optimistic child: a proven program to safeguard children against depression and build lifelong resilience - "Seligman, Martin E. P." (Boston, 2007)
In the face of increasing levels of depression affecting American children, a new edition of the best-selling guide to preventing childhood depression shows parents and educators how to instill optimism, resilience, and confidence in children, enabling them to feel self-reliant, boost self-esteem, and perform better in school. Reprint.
Keywords: Optimism in children